2021
DOI: 10.1021/acsaem.1c02835
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Magnetic Phase-Change Microcapsules with Black Phosphorus Nanosheets for Efficient Harvest of Solar Photothermal Energy

Abstract: Solar photothermal energy storage using phasechange material (PCMs) provides sustainable penetration in comprehensive utilization. However, PCMs are obliged to suffer from low conversion and storage effectiveness in solar photothermal energy due to a low optical absorption capacity. In this study, we developed a type of magnetic phase-change microcapsule system with superior photothermal energy conversion efficiency. The microcapsule system was constructed with n-docosane as a PCM core and a CaCO 3 /Fe 3 O 4 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 56 publications
2
20
0
Order By: Relevance
“…They also showed good thermal resistance and high thermal cycle stability. To resolve the leakage problem during the phase transition from solid to liquid that results in poor cycle stability and durability of PCMs, Liu’s group microencapsulated the PCMs with CaCO 3 /Fe 3 O 4 composite shells. CaCO 3 is considered to be suitable as a wall of material for the microencapsulation of PCMs because it has a rigid and tight nature, high thermal conductivity, low cost, and requires mild synthetic condition. To achieve high solar–thermal-conversion efficiency, Fe 3 O 4 nanoparticles, that have an ability to accelerate photothermal energy conversion and storage, were incorporated.…”
Section: Solar Thermal Conversion Materialsmentioning
confidence: 99%
“…They also showed good thermal resistance and high thermal cycle stability. To resolve the leakage problem during the phase transition from solid to liquid that results in poor cycle stability and durability of PCMs, Liu’s group microencapsulated the PCMs with CaCO 3 /Fe 3 O 4 composite shells. CaCO 3 is considered to be suitable as a wall of material for the microencapsulation of PCMs because it has a rigid and tight nature, high thermal conductivity, low cost, and requires mild synthetic condition. To achieve high solar–thermal-conversion efficiency, Fe 3 O 4 nanoparticles, that have an ability to accelerate photothermal energy conversion and storage, were incorporated.…”
Section: Solar Thermal Conversion Materialsmentioning
confidence: 99%
“…The MSR thin layer shelters PCM from leakage above its melting point and also provides the PCC with outstanding thermal reliability. By comparing with the relevant work, our work creates a novel assembly form to prepare functional macroencapsulated PCCs, which allows the uniform and spatial distribution of PCMs and photothermal conversion particles, guaranteeing the relatively high photothermal conversion capacity and exothermic accuracy of composites. In general, PCM@PUF-CuS@MSR is a cheap, difunctional, and macroencapsulated PCC with a core–shell structure which is acquired from MPCMs, demonstrating great potential as an energy storage medium for low-temperature solar energy storage, such as domestic solar water heaters, photothermal cells based on PCMs, and so on. , …”
Section: Introductionmentioning
confidence: 98%
“…In fact, copper sulfide has been used in PCM microcapsules to prepare solar energy conversion and storage PCM microcapsules by filling CuS nanoparticles into the PCMs or shell . Several other studies also reported solar-driven energy storage microcapsules prepared by surfactant-stabilized emulsion with CNTs, Fe 3 O 4 , PDA, or black phosphorus as photothermal materials. These nanoparticles were integrated into the shell of the PCM microcapsules as photothermal conversion functional fillers.…”
Section: Introductionmentioning
confidence: 99%